Analisis Asesmen Sumatif pada Pembelajaran Bahasa Indonesia Fase E - Dj S, Intan Kholida; Suryani, Irma; Abrar, Mukhlash (STKIP Siliwangi, 2024)
The aim of this research is to describe the results of summative assessments in Indonesian language learning. The research uses qualitative methods with descriptive presentation. Primary data was taken from the results of the final year assessment of MA Al-Khairiyah students. The primary data source comes from carrying out year-end assessments at MA Al-Khairiyah. Participants in this research were class X students at MA Al-Khairiyah. The data collection technique in this research is documentation. Documentation techniques are used to document each activity carried out. Research data analysis uses an interactive model through data reduction, data displays, and conclusions. Based on the results of the analysis of summative assessments in Indonesian language learning, students' learning achievements can be seen from the completed learning. As many as seven out of fifteen students still have not reached the standard criteria for achieving learning objectives. To achieve predetermined learning outcomes, educators must improve the learning process or revise strategies for implementing further learning.